2018
DOI: 10.3847/1538-4357/aad27e
|View full text |Cite
|
Sign up to set email alerts
|

ALMA Observations of the Solar Chromosphere on the Polar Limb

Abstract: We report the results of the Atacama Large Millimeter/sub-millimeter Array (ALMA) observations of the solar chromosphere on the southern polar limb. Coordinated observations with the Interface Region Imaging Spectrograph (IRIS) are also conducted. ALMA provided unprecedented high spatial resolution in the millimeter band (≈ 2.0 ′′ ) at 100 GHz frequency with a moderate cadence (20 s). The results are as follows: (1) The ALMA 100 GHz images show saw-tooth patterns on the limb, and a comparison with SDO/AIA 171Å… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 34 publications
4
26
0
1
Order By: Relevance
“…The first high-resolution images of the quiet Sun in the millimeter range were obtained by White et al (2006) and Loukitcheva et al (2006) who used the Berkeley-Illinois-Maryland Association Array (BIMA) to obtain ∼ 10 ′′ resolution. With the advent of ALMA a new generation of high-resolution millimeterwavelength images has been forming (e.g., Bastian et al, 2017;Shimojo et al, 2017a,b;Nindos et al, 2018;Yokoyama et al, 2018;Jafarzadeh et al, 2019;Loukitcheva et al, 2019;Molnar et al, 2019;Patsourakos et al, 2020;Wedemeyer et al, 2020) and an example is presented in Figure 2. The figure indicates that the chromospheric network, delineated in the AIA 1,600 Å image, is the dominant structure in the radio images.…”
Section: Imaging Observations Of the Non-flaring Sunmentioning
confidence: 99%
“…The first high-resolution images of the quiet Sun in the millimeter range were obtained by White et al (2006) and Loukitcheva et al (2006) who used the Berkeley-Illinois-Maryland Association Array (BIMA) to obtain ∼ 10 ′′ resolution. With the advent of ALMA a new generation of high-resolution millimeterwavelength images has been forming (e.g., Bastian et al, 2017;Shimojo et al, 2017a,b;Nindos et al, 2018;Yokoyama et al, 2018;Jafarzadeh et al, 2019;Loukitcheva et al, 2019;Molnar et al, 2019;Patsourakos et al, 2020;Wedemeyer et al, 2020) and an example is presented in Figure 2. The figure indicates that the chromospheric network, delineated in the AIA 1,600 Å image, is the dominant structure in the radio images.…”
Section: Imaging Observations Of the Non-flaring Sunmentioning
confidence: 99%
“…While the first regular ALMA observations of the Sun were only offered in Cycle 4 with a first solar campaign in December 2016, earlier observations from Commissioning and Science Verification (CSV) campaigns have been made publicly available. Both regular and CSV data are already used in publications: Alissandrakis et al (2017), Bastian et al (2017), Shimojo et al (2017b), Brajša et al (2018), Nindos et al (2018), Yokoyama et al (2018), Jafarzadeh et al (2019), Loukitcheva et al (2019), Molnar et al (2019), Rodger et al (2019), Selhorst et al (2019), Patsourakos et al (2020), da Silva Santos et al (2020.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown the potential of ALMA to examine distinct phenomena both in quiet and active regions [31][32][33][34][35][36][37][38][39][40]. In particular, Eklund et al [41] found signatures of shock-wave events in Band 3 (2.8-3.3 mm) observations from December 2016, coming to the conclusion that there are numerous small-scale dynamic structures with lifetimes of 43-360 s present in the ALMA field of view (FOV), with excess temperatures of more than 400 K and a correlation between their occurrence and the magnetic field strength.…”
Section: Introductionmentioning
confidence: 99%